pt đa thức sau -> ntử:
\(x^4+2016x^2+2015x+2016\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
2015x4 + 2016x2 + x + 2016
= (2015x4 + 2015x3 + 2015x2) + (- 2015x3 - 2015x2 - 2015x) + (2016x2 + 2016x + 2016)
= (x2 + x + 1)(2015x2 - 2015x + 2016)
Ta có: x^4 + 2016x^2 + 2015x + 2016
= x^4 + x^3 + x^2 - x^3 - x^2 - x + 2016x^2 + 2016x + 2016
= x^2(x^2 + x + 1) - x(x^2 + x + 1) + 2016(x^2 + x + 1)
= (x^2 + x + 1)(x^2 - x + 2016)
\(x^4+2016x^2+2015x+2016\)
\(=x^4-x+2016x^2+2016x+2016\)
\(=x\left(x^3-1\right)+2016\left(x^2+x+1\right)\)
\(=x\left(x-1\right)\left(x^2+x+1\right)+2016\left(x^2+x+1\right)\)
\(=\left(x^2+x+1\right)\left(x^2-x+2016\right)\)
Tính giá trị của đa thức:
P(x) = x^{2017}-2016x^{2016}-2016x^{2015}-...--2016x^2^-2016x+1 tại x=2017
bạn có: x^4 + 2016x^2 + 2015x + 2016
= x^4 + x^3 + x^2 - x^3 - x^2 - x + 2016x^2 + 2016x + 2016
= x^2(x^2 + x + 1) - x(x^2 + x + 1) + 2016(x^2 + x + 1)
= (x^2 + x + 1)(x^2 - x + 2016)
\(x^4+2016x^2+2015x+2016\)
=\(x^4+x^3+x^2+2015x^2+2015x+2015+1-x^3\)
=\(x^2\left(x^2+x+1\right)+2015\left(x^2+x+1\right)+\left(1-x\right)\left(x^2+x+1\right)\)
=\(\left(x^2+x+1\right)\left(x^2+2015+1-x\right)\)
=\(\left(x^2+x+1\right)\left(x^2-x+2016\right)\)
\(=x^4-x+2016x^2+2016x+2016.\)
\(=x\left(x^3-1\right)+2016\left(x^2+x+1\right)\)
\(=x\left(x-1\right)\left(x^2+x+1\right)+2016\left(x^2+x+1\right)\)
\(=\left(x^2+x+1\right)\left(x^2-x+2016\right)\)
\(=x^4-x+2016x^2+2016+\)\(2016\)
\(=x\left(x^3-1\right)+2016\left(x^2+x+1\right)\)
\(=x\left(x-1\right)\left(x^2+x+1\right)+2016\)\(\left(x^2+x+1\right)\)
\(=\left(x^2+x+1\right)\left(x^2-x+2016\right)\).